Is there an association between a plant-based eating pattern and clinical findings of a migraine headache? - Karimi, Elham; Tirani, Shahnaz Amani; Azimi, Elham Sadat; Askari, Gholamreza; As’habi, Atefeh; Arab, Arman (Frontiers in Nutrition, 2023)
Aims The present study was conducted among Iranian individuals diagnosed with migraine headaches to investigate the association between plant-based eating patterns and the clinical features of a migraine headache. Methods In total, 262 patients aged 20–50 years who were diagnosed with migraine headaches were included in the current cross-sectional study. Participants’ dietary intake was assessed using a validated 168-item, semi-quantitative food frequency questionnaire (FFQ). Three versions of the plant-based diet index (PDI) comprising overall PDI, healthy PDI (hPDI), and unhealthy PDI (uPDI) were generated. Headache frequency, duration, and severity were assessed via a 30-day headache diary. Migraine-related disability was assessed with a validated version of the headache impact test (HIT-6) questionnaire. Serum nitric oxide (NO) was measured using the Griess method utilizing serum samples. Results After controlling for potential confounders, an increase in mean PDI score from 48.22 to 61.67 decreased the frequency of headaches by −2.95 (95% CI: 0.06, 0.53; ptrend = 0.005). PDI was inversely associated with serum levels of NO in those with the highest scores of PDI compared to those with the lowest scores after adjustment for confounders (β = −7.69; 95% CI: −14.68, −0.69; ptrend = 0.028). After adjustment for potential confounders, an increase in the mean hPDI score from 47.96 to 65.25 decreased serum levels of NO by −11.92 (95% CI: −19.74, −4.10; ptrend = 0.003). Conclusion Our findings suggest that higher adherence to a plant-based eating style, as evidenced by higher PDI and hPDI values, was significantly associated with lower headache frequency and serum levels of NO.